Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/1071100713509804
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Study on the Percutaneous Treatment of Displaced Intra-articular Fractures of the Calcaneus

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
1
19
1
1
Order By: Relevance
“…Closed reduction and percutaneous fixation have been widely reported to significantly reduce the incidence of wound healing complications. De Vroome et al reported that postoperative infection occurred in 1 of 46 (2.4%) cases treated using closed reduction and percutaneous screw fixation [25]. However, this treatment seems to be more suitable for cases with moderately displaced fracture or non-comminuted calcaneus fracture because of the limited fixation strength.…”
Section: Discussionmentioning
confidence: 99%
“…Closed reduction and percutaneous fixation have been widely reported to significantly reduce the incidence of wound healing complications. De Vroome et al reported that postoperative infection occurred in 1 of 46 (2.4%) cases treated using closed reduction and percutaneous screw fixation [25]. However, this treatment seems to be more suitable for cases with moderately displaced fracture or non-comminuted calcaneus fracture because of the limited fixation strength.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy still exists regarding their classification, treatment, and postoperative management, as well as the appropriate operative technique for this type of fracture; therefore, calcaneal fractures remain among the most challenging fractures for orthopaedic surgeons to treat. Closed reduction with percutaneous pinning, a minimally invasive technique, is believed to result in fewer soft tissue injuries and fewer wound complications [ 2 ]. Indications for this technique include the following: (a) Sanders 2C tongue-type fractures; (b) displaced calcaneal tuberosity fractures; (c) temporary stabilization of fractures with severe soft tissue compromise; and (d) fractures in patients with relative contraindications to open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…2The published rate of arthrodesis is between 0 and 15% after minimally invasive surgery: 0-12% after ORIF, and 3.8-17% after conservative means. (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) The subtalar arthrodesis rate of 0% described by Park et al was based on a relatively low number of patients and only one year follow-up. (29) In extremely complex intra-articular fractures, a primary subtalar arthrodesis is postulated to achieve satisfactory results.…”
Section: Discussionmentioning
confidence: 99%